Comparison of meat yield and physicochemical characteristics of indigenous, cockerel and sonali chicken - Sarker, MAH; Hossain, ME; Habib, M; Hashem, MA; Ali, MS (Meat Research, 2022)
The experiment was conducted to compare the meat yield and quality characteristics of indigenous, cockerel and sonali male (Backcrossed; RIR♂ × Sonali♀) chicken weighing around 750g. The birds were slaughtered and meat yield characteristics such asbreast, thigh, drumstick, wing, liver, heart, head, gizzard, neck etc. were compared against their live weight. After that the breast, thigh and drumstick of all birds were stored at 4 ̊C to evaluate different quality characteristics at 24hour postmortem. No significant differences (p>0.05) were found in meat yield characteristics among indigenous, cockerel and sonali chicken except dressing percentage. Highly significant (p<0.001) differences were observed in dressing percentage among three types of chicken. Dressing percentage was significantly higher (p<0.001) in indigenous chicken compared to cockerel and sonali chicken. In proximate composition, no significant differences (P>0.05) were found in dry matter, ash, moisture and crude protein content among the breast meat of three types of chicken but the ether extract content was significantly higher in indigenous chicken breast meat compare to cockerel and sonali chicken (P<0.05). The pH of breast and thigh meat at 24-hour postmortem and the instrumental color (CIE L* a* b*) of breast, thigh and drumstick meat at 2- hour (on-rigor) and 24-hour (post-rigor) postmortem did not differ among the three types of chicken. Highly significant differences (p<0.01) in water holding capacity of breast, thigh and drumstick meat were found, although no significant differences (P>0.05) were found in cooking loss and drip loss among the three types of chicken. Water holding capacity was significantly lower in breast meat, but higher in thigh and drumstick meat in case of cockerel compare to other two types of chickens.